2018
DOI: 10.1101/373472
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

TCRex: detection of enriched T cell epitope specificity in full T cell receptor sequence repertoires

Abstract: Identification of T-cell receptor (TCR) repertoire epitope targets constitutes an important part of many TCR repertoire studies. To date, we are still relying on time consuming epitope binding experiments for the identification of epitope-specific TCR sequences. Recently, we showed that the prediction of epitope-TCR interaction is possible using a random forest model. We implemented this method in a webtool called TCRex. TCRex is the first tool that enables the prediction of TCR-epitope recognition. It allows … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 32 publications
0
14
0
Order By: Relevance
“…Although we do not fully understand the factors underlying TCR-pMHC recognition, recent studies have shown that T cells binding to a particular pMHC share common TCR sequence features and, in select cases, it is possible to predict the binding probability of an unseen TCR sequence based on learned TCR sequence features (13)(14)(15)(16)(17)(18)(19)(20)(21). However, these studies either were limited by the quantity and diversity of training data generated by traditional single multimer sorting or antigen reexposure assays or suffered from the challenging normalization issues associated with multi-omic characterization of T cells (22).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although we do not fully understand the factors underlying TCR-pMHC recognition, recent studies have shown that T cells binding to a particular pMHC share common TCR sequence features and, in select cases, it is possible to predict the binding probability of an unseen TCR sequence based on learned TCR sequence features (13)(14)(15)(16)(17)(18)(19)(20)(21). However, these studies either were limited by the quantity and diversity of training data generated by traditional single multimer sorting or antigen reexposure assays or suffered from the challenging normalization issues associated with multi-omic characterization of T cells (22).…”
Section: Introductionmentioning
confidence: 99%
“…As next-generation screening technologies have increased the volume of available TCR-pMHC binding data, robust classifiers to computationally validate and subsequently predict TCR-pMHCspecific recognition are desired. While the results from initial TCR-pMHC binding classifiers are encouraging, most of them were only trained using CDR loop sequences or -chain sequences alone and thus unable to learn the overall complex sequence patterns from full-length TCR sequences, resulting in suboptimal prediction accuracy for highly diverse pMHC binding TCRs (13,14,19,20). Leveraging the ability of deep learning algorithms to learn complex patterns, a couple of neural network-based classifiers were recently proposed (17,18) to uncover binding patterns in large, highly complex pMHC binding TCR sequences.…”
Section: Introductionmentioning
confidence: 99%
“…Most are constructed based on data from the IEDB, VDJdb, and/or McPAS-TCR and, in addition to the epitope information, make use of either CDR3β sequences alone [13][14][15] , a mixture of CDR3α and CDR3β sequences 16 , or smaller data sets entailing all 6 CDR3 sequences and potentially additional cellular information 17,18 . Methodologically, the different studies range from simple CDR3β alignmentbased methods 19,22 , over CDR similarity-weighted distances such as TCRdist 7 , k-mer feature spaces in combination with PCA and decision trees (SETE 13 ), random forests 20,21 such as TCRex 23 , CNN-based (ImRex) 16 , and Gaussian process classification methods (TCRGP 17 ), to more complex approaches integrating natural language processing (NLP) methods (ERGO 14 ). The overall conclusion from these earlier works is that while the prediction of TCR specificity is feasible, the volume and accuracy of current data limit the performance of the developed models.…”
mentioning
confidence: 99%
“…Our co-authors' group recently implemented a phase I clinical trial to evaluate the effects of CD200-blockade in the GBM6-AD lysate vaccine in patients with recurrent high-grade gliomas (NCT04642937). To improve the design of our future vaccine studies, the use of novel algorithms developed for the identification of target epitopes recognized by the TCR repertoire (31,32) may allow us to identify the antigenic targets.…”
Section: Discussionmentioning
confidence: 99%